Design a Wideband low-noise amplifier for wireless communication using 0.35-¡Łm CMOS technology - Mohd Hafiz Abu
This final year project is to design a wideband low noise amplifier by using mentor graphic software using 0.35-tsmc CMOS process technology for design and simulation.